2020
DOI: 10.1101/2020.11.16.379412
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HOX13-MEDIATEDDBX2REGULATION IN LIMBS SUGGESTS INTER-TAD SHARING OF ENHANCERS

Abstract: BackgroundDuring tetrapod limb development, the HOXA13 and HOXD13 transcription factors are critical for the emergence and organization of the autopod, the most distal aspect where digits will develop. Since previous work had suggested that the Dbx2 gene is a target of these factors, we set up to analyze in detail this potential regulatory interaction.ResultsWe show that HOX13 proteins bind to eutherian-specific sequences at the vicinity of the Dbx2 locus that have enhancer activity in developing digits. Howev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…As expected, the detected interactions are strongly enriched within the same TAD 23,29,48 . However, multiple cross-TAD contacts are still observed in CHi-C data 23,29,48 , and a recent study 52 has provided evidence that such contacts may play a functional role in developmental gene control.…”
Section: Limitationsmentioning
confidence: 99%
“…As expected, the detected interactions are strongly enriched within the same TAD 23,29,48 . However, multiple cross-TAD contacts are still observed in CHi-C data 23,29,48 , and a recent study 52 has provided evidence that such contacts may play a functional role in developmental gene control.…”
Section: Limitationsmentioning
confidence: 99%
“…Deletion, translocation, or disruption of this locus can reportedly cause camptodactyly, syndactyly, brachydactyly, ectrodactyly, and polydactyly 14,19 . Considering the current case study, the deletion contained HOXD13 , an essential gene for regulating and developing the genital tract and autopod that forms hands and feet 20 . In addition, it has been suggested that the HOXD cluster can regulate the size and number of digits in a dose‐dependent manner, indicating a negative relationship between the HOXD gene and digit number rather than qualitative functions 21,22 .…”
Section: Discussionmentioning
confidence: 80%
“… 14 , 19 Considering the current case study, the deletion contained HOXD13 , an essential gene for regulating and developing the genital tract and autopod that forms hands and feet. 20 In addition, it has been suggested that the HOXD cluster can regulate the size and number of digits in a dose‐dependent manner, indicating a negative relationship between the HOXD gene and digit number rather than qualitative functions. 21 , 22 In the presence of multiple homozygous HOXD mutations, major limb defects are likely to occur.…”
Section: Discussionmentioning
confidence: 99%
“…CUT and RUN libraries were sequenced paired-end on a HiSeq4000 sequencer and processed as in 26 , mapped either on mm10 or on the II1TDOM-542 mutant genome. The E11.5 whole-forelimb HOXA13 and HOXD13 ChIP-Seq datasets (SRR3498934 of GSM2151013 and SRR3498935 of GSM2151014) as well as E12.5 distal and proximal forelimb H3K27Ac and CTCF ChIP-Seq datasets (SRR5855214 of GSM2713703, SRR5855215 of GSM2713704, SRR5855220 of GSM2713707, and SRR5855221 of GSM2713708) were processed similarly to what has been previously published 56 . Adapter sequences and bad quality bases were removed with Cutadapt 57 version 1.16 with options -a GATCGGAAGAGCACACGTCTGAACTCCAGTCAC -A GATCGGAAGAGCGTCGTGTAGGGAAAGAGTGTAGATCTCGGTGGTCGCCGTATCATT -q 30 -m 15 (−A being used only in PE data sets).…”
Section: Methodsmentioning
confidence: 99%